Attracting Attention in a Limited Attention World: Exploring the Causes and Consequences of Extreme Positive Earnings Surprises - Koester, Allison; Lundholm, Russell; Soliman, Mark (Management Science, 2016)
We investigate why extreme positive earnings surprises occur and the consequences of these events. We posit that managers know before analysts when extremely good earnings news is developing, but can have incentives to allow the earnings news to surprise the market at the earnings announcement. In particular, managers can use an extreme positive earnings surprise to attract investor attention when they believe their stock is neglected and future performance is expected to be strong. Analysts, who must allocate scarce resources across many firms, can also be inattentive and miss signals that suggest good performance is going to be announced. Using various proxies for extreme positive earnings surprises, management expectations for future performance and desire for attention, and analyst neglect, we find evidence that an extreme positive earnings surprise is a predictable event. These findings are incremental to controlling for a firm’s information environment, earnings volatility, and operating leverage. Finally, we show that extreme positive earnings surprises are a successful method for attracting attention, with significant increases in the number of institutional owners, the number of analysts, and trading volume during the subsequent three years. This paper was accepted by Mary Barth, accounting.